Guns and butter the tradeoff between defense and social expenditure in the Philippines (1981-2022) - Bulawan, Axl Fitzgerald L. (2024)
Tradeoffs, as a result of scarcity, is at the center of economics. One common tradeoff is the guns and butter, the budgetary tradeoff between defense expenditure and social expenditure. Using Budget of Expenditures and Sources of Funding (BESF) data from 1981 to 2022, this study used regression analysis to determine whether this tradeoff exists in the case of the Philippines. It found no evidence that increased defense expenditure has a negative effect on social expenditure, as represented by education expenditure. On the contrary, it found that defense expenditure induces education expenditure. This study also attempted to test the Benoit hypothesis using Philippine data, a hypothesis that posits that defense spending results to economic growth. Building on Dariano's (2015) earlier work, this study used Granger causation analysis to determine the casual relationship between defense expenditure and social expenditure to GDP and vise versa. It found that social expenditure Granger causes economic output, while no appropriate lag order length was selected to be able to prove the Benoit hypothesis. Results imply the need for greater budgetary allocation to social spending in order to increase economic output.